2019
DOI: 10.3389/fcimb.2019.00415
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Acute Exacerbation of Chronic Rhinosinusitis

Abstract: Background: Acute exacerbations of chronic rhinosinusitis (CRS) have been increasingly recognized as an important disease entity with a significant impact on the quality of life. There is a growing amount of research on the etiopathogenesis and management of acute exacerbations of CRS. This review aims to summarize the current literature and provide an overall understanding of acute CRS exacerbations.Methods: A related literature review with the key terms of “chronic rhinosinusitis” and “exacerbation” was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Since these criteria were introduced, there has been limited work on AECRS. There have been 3 studies utilizing the suggested definition from the 2016 ICAR document, including 1 literature review and 2 cohort studies which used but did not assess the definition 29,210,211 …”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these criteria were introduced, there has been limited work on AECRS. There have been 3 studies utilizing the suggested definition from the 2016 ICAR document, including 1 literature review and 2 cohort studies which used but did not assess the definition 29,210,211 …”
Section: Definitionsmentioning
confidence: 99%
“…Consensus guidelines and expert opinion recommend short‐term antibiotics for AECRS, in the setting of a positive culture to provide symptomatic relief 1,31 . The treatment for ARS with the implementation of antibiotics has been extrapolated and applied to AECRS, despite AECRS being recognized as a distinct entity from ARS 210,1760 Antibiotics and treatment of the preexisting CRS are often implemented.…”
Section: Acute Exaccerbation Of Chronic Rhinosinusitis (Aecrs)mentioning
confidence: 99%
“…The host immune response to a viral infection consists of non-specific and specific components, which will eventually eliminate the invading agent, but also generate dead epithelial and immune cells, creating an environment opportune for secondary bacterial infections. During viral infection in chronic RS, a similar inflammatory process can occur as in acute RS [152,153].…”
Section: Chronic Rhinosinusitis (Crs)mentioning
confidence: 95%
“…In terms of the differences in reporting URTIs, Wu et al elucidated the difficulties in defining acute exacerbations of CRS 27 and highlighted that others had used various metrics to measure this including the number of patientreported "sinus infections," CRS-related antibiotic courses, and CRS-related oral corticosteroid courses. [28][29][30] These are of course subjective metrics on the part of the patient and clinician, and in practice, it will be difficult to separate viral URTIs from bacterial episodes.…”
Section: Discussionmentioning
confidence: 99%